ACC and Community Responsibility - Wilson, Garry (Victoria University of Wellington Law Review, 2004)
The author, the then-Chief Executive of the Accident Compensation Corporation (ACC), provides his thoughts on the ACC scheme as the last presentation of an Accident Compensation conference. He describes New Zealand as a country that has created an idealistic country where reformist law-makers have long endeavoured to ensure that all citizens have an acceptable standard of living, regardless of their circumstances. ACC's overarching role remains to contribute to a nation where there are fewer injuries and where those injured return quickly to well-being. The author speaks highly of the ACC scheme, then having high satisfaction rates and private medical institutions taking on ACC methodologies. It is concluded that the ACC scheme is serving the community more efficiently and imaginatively than would have been thought possible in 1974.